Organizational Climate of State-Owned Enterprise and Efficiency of Managing and Organization - VARII, Myron J.; LESHCHYNSKA, Olena A.; MAKARENKO, Stefaniia S.; OLIINYK, Alla V.; ZAKALYK, Halyna M. (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
The article presents the results of the research of mutual influence of the organizational climate of the Ukrainian state-owned enterprise and the processes of managing an organization. The sample was drawn of 72 respondents from all divisions of Ukrposhta Lviv State-Owned Enterprise. The questionnaire developed by A. Maier to evaluate the degree of optimality of the organizational climate, the test to evaluate the effectiveness of the head developed by S. Roshchin and indicators of organizational efficiency model developed by V. Sate were used for data collection. The linear correlation coefficient was used to check the hypothesis on the interrelation between climate indicators and its impact on management. The obtained results were presented using the correlation analysis and the method of correlation pleiades. The correlation pleiad obtained in the result of the research showed a conspicuous tendency to the connection of the indicators of satisfaction with work schedule, level of salary and stability of the workplace with relations with colleagues, attitude to work, opportunity and desire for professional development as well as the authority of the direct supervisor and the quality of his decisions.